Paraíso e inferno: releituras do imaginário medieval em A Dama Pé-de-cabra - Dezidério, Felipe Hélio da Silva (2013)
This dissertation has as investigative goal the work of interpretation of medieval sources done by Alexander Herculano while composing “The Lady with the Cloven Hoof”. It is seen that the narrative recovers part of the medieval imaginary present in the genealogical text. As result of trying to recreate the medieval way of noticing reality, the settings and characters of the narrative simbolize and mark a conception of medieval world, ilustrated sometimes by the presence of supernatural phenomena through the story. Therefore, it is the interest of this dissertation to point out which measurement of the author’s romantic perspective alters or retakes the medieval meanings that imply the narrative’s structure. Eventually, another investigated point through this work will be the way that the dualism of medieval thought between the sacred and the profane, center and periphery, countryside and city, male and female are retrivied and structure character’s behavior from the narrative. The events of fantastic marvelous character present in the story would be a result of the confrontation between these opposite pairs. Part of this duel occurs in desolated or wild settings that coincide with the manifestation of supernatural phenomena in some moments; fact that allows pondering a probable relation between wild settings and the occurrence of fantastic marvelous events in the plot. The analysis of these narrative elements will be sustained by the perspective of the mentality and of the imaginary, terms coined and developed through the 60s by the participants of History of Mentalities, which features names such as Jacques Le Goff and Georges Duby. The concepts of this historical trend allow aproximations to Literature, as a way that the elements ordered in the virtuality of the literary text and its intern relations are investigated inside of a subtle web of representations that allow retrieving and interpreting part of the meanings of implied sources to the literary work, such as setting, time, characters and the way how these structures relate in the narrative’s plot.